Premium rush [videorecording (DVD)] - Koepp, David; Ramirez, Dania; Chung, Jamie, 1983-; Gordon-Levitt, Joseph, 1981-; Shannon, Michael, 1974-; Mandvi, Aasif, 1966- (Sony Pictures Home Entertainment, 2012)
In Manhattan, a bike messenger picks up an envelope that attracts the interest of a dirty cop, who pursues the cyclist throughout the city.